New species and records of Burmagomphus Williamson, 1907 (Odonata, Gomphidae) from China - Zhang, Hao-Miao; Kosterin, Oleg E.; Cai, Qing-Hua (Zootaxa, 2015)
Four new species of Burmagomphus Williamson, 1907 are described from Southwestern China: B. apricus sp. nov. from Xishuangbanna National Nature Reserve, Menglun Town, Xishuangbanna Dai Autonomous Prefecture, Yunnan Province; B. magnus sp. nov. from Huayudong, Nanxi Town, Hekou County, Hani-Yi Autonomous Prefecture of Honghe, Yunnan Province, B. dentatus sp. nov. from Zhangjiang River in Xiaoqikong scenic spot, altitude 400 m, Libo County, Guizhou Province, and B. latescens sp. nov. from Sifangjing, Mengding Town, Gengma County, Lincang City, Yunnan Province. New records of Burmagomphus spp. in China are provided, with B. asahinai and B. williamsoni williamsoni for the first time reported from China. A revised checklist of Burmagomhus spp. of China is provided which includes 14 species. A doubtful record of B. arboreus and relations of the newly described species are discussed. All types are deposited in the Collection of Aquatic Animals, Institute of Hydrobiology, Chinese Academy of Sciences, Wuhan City, Hubei Province, China.